Revision of the gumilline genus Nilionympha with a new species from the Middle Jurassic of China (Neuroptera: Osmylidae) - Li, Qinghua; Ren, Dong; Wang, Yongjie (Zootaxa, 2018)
The poorly known genus Nilionympha Ren and Engel, 2007 in the subfamily of Gumillinae is updated and revised based on the reexamination of the type specimens and description of a new species Nilionympha shantouensis sp. nov. from the Middle Jurassic Jiulongshan Formation of Daohugou, Inner Mongolia, China. A further comparison between Nilionympha and other gumilline genera is provided to corroborate the generic status according to the updated diagnostic characters of forewing. The species Nilionympha imperfecta Ren and Engel, 2007 is transferred to the genus of Enodinympha.